2015
DOI: 10.1016/j.tetlet.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted tertiary and O-substituted quaternary carbon stereogenic centers by site-, diastereo- and enantioselective vinylogous Mannich reactions

Abstract: A readily accessible small-molecule phosphine, derived from commercially available starting materials such as an enantiomerically pure amino acid, serves as the precursor to a Ag-based chiral complex that can be prepared and used in situ to promote a variety of enantioselective vinylogous Mannich (EVM) reactions that involve siloxypyrroles as reaction partners. Transformations with unsubstituted nucleophilic components proceed efficiently and with exceptional site- (γ vs α-addition), diastereo- and enantiosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Quinuclidine and DBU have nucleophilic characteristics that promote the reaction, implying an MBH mechanism for enolate formation (entries 9 and 10); much less nucleophilic Et 3 N exhibited steady reaction progress to give the α‐adduct 3 a (entry 7) . Together with the exclusive formation of α‐adduct 3 a with lithium aryloxide as Brønsted base (entry 8), the dienolate formation/α‐addition/isomerization sequence was likely operative to afford MBH‐type α‐adduct 3 a . Lowering the reaction temperature led to improved enantioselectivity (91 % ee ; entry 11) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinuclidine and DBU have nucleophilic characteristics that promote the reaction, implying an MBH mechanism for enolate formation (entries 9 and 10); much less nucleophilic Et 3 N exhibited steady reaction progress to give the α‐adduct 3 a (entry 7) . Together with the exclusive formation of α‐adduct 3 a with lithium aryloxide as Brønsted base (entry 8), the dienolate formation/α‐addition/isomerization sequence was likely operative to afford MBH‐type α‐adduct 3 a . Lowering the reaction temperature led to improved enantioselectivity (91 % ee ; entry 11) .…”
Section: Methodsmentioning
confidence: 99%
“…[19] To gether with the exclusive formation of a-adduct 3a with lithium aryloxidea sB r ønsted base (entry 8), [20] the dienolate formation/a-addition/isomerization sequence was likely operative to afford MBH-type a-adduct 3a. [21] Lowering the reaction temperature led to improved enantioselectivity (91 % ee;e ntry 11). [22] Et 3 Ni sa ni nexpensive common amine base, and the use of 2equiv of Et 3 Na t ah igherc oncentrationa fforded 3a in 94 %i solated yield with 90 % ee (entry 12).…”
mentioning
confidence: 99%
“…Finally, the same authors reported the first example of an asymmetric VMR with 5-methyl-substituted silyloxyfuran 12, resulting in the formation of butenolides 14 bearing an O-substituted quaternary stereogenic center (Scheme 5). 13 Addition to different aldimines 13 proceeded with high diastereo-and enantioselectivity although variable amounts of α-addition products were detected, probably due to the lower nucleophilicity and accessibility of the γ site.…”
Section: Asymmetric Vinylogous Mannich Reactions (Vmr) With 2-silyloxmentioning
confidence: 99%
“…Additions to aryl-and alkynyl-substituted aldimines 10 took place in good yields, furnishing compounds 11 bearing two contiguous N-substituted stereogenic centers with exceptional site-(γ-vs α-addition), diastereo-and enantioselectivity (Scheme 4). 13 Scheme 4 Asymmetric Ag-catalyzed VMR of aryl-and alkynyl-substituted aldimines 10 and N-Boc TMS-silyloxypyrrole 9…”
Section: Asymmetric Vinylogous Mannich Reactions (Vmr) With 2-silyloxmentioning
confidence: 99%
“…[8]的不对称加成、Mannich 反应[9]、亚胺的烯丙基化反应[10] [11] [12]等多种反应中都表现出良 INOVA-600 型核磁共振仪(以 TMS 为内标,CDCl 3 为溶剂);Brucker Equinox 55 FT-TR 型红外光谱仪 (KBr 压片);Brucker 型质谱仪(ESI 电离技术);低温实验使用 EYELA PSL-1810 型磁力搅拌低温恒温水槽 (无水乙醇为介质)。 实验所用试剂均为分析纯,石油醚沸程为 60℃~90℃,其中,无水四氢呋喃是在钠砂中惰性气体保护 下加热回流并用二苯甲酮显色;柱层析硅胶 G (青岛海洋化工有限公司);薄层层析硅胶 GF254 (青岛海洋 化工有限公司);薄层层析板(GF254,加 0.5% CMC 自制),紫外灯下(254 nm)观测并用碘蒸气显色。 2.2. 氨基酚化合物的合成 以化合物 7A 的合成为例[10]: 50 mL 圆底瓶中加入化合物 1A (0.23 g, 2 mmol),添加混合溶剂(20 mL, V 1,4-二氧六环:V 水 = 1:1)搅拌使其 溶解溶液。冰浴条件下分批加入(Boc) 2 O (1.09 g, 5 mmol, 2.5 equiv.…”
unclassified